Quad S2-Alar-Iliac Screw Fixation via Navigated Spinal Robotics With Software Planning: 2-Dimensional Operative Video. Issue 5 (5th June 2020) - Pham, Martin H; Diaz-Aguilar, Luis Daniel; King, Bradley H; Osorio, Joseph A; Lehman, Ronald A
Abstract: The use of robotic guidance for spinal instrumentation has become promising for its ability to offer the advantages of precision, accuracy, and reproducibility. However, utilization and adoption of robotic platforms for spine surgery remain limited especially in comparison to other surgical fields. We present here a case of a 71-yr-old man with a prior T4-pelvis long-segment fusion who presented with distal sacro-iliac instrumentation loosening with pseudarthrosis. He subsequently underwent construct revision with quad (bilateral dual) S2-alar-iliac screw fixation with navigated spinal robotic assistance (Mazor X Stealth Edition, Medtronic Sofamor Danek, Medtronic Inc, Dublin, Ireland). To our knowledge, this is the first video demonstrating the preoperative software planning and intraoperative workflow for placing quad S2-alar-iliac screws with navigated spinal robotic guidance using the Mazor X Stealth Edition.  There is no identifying information in this video. Patient consent was obtained for the surgical procedure and for publishing of the material included in the video.